2010
DOI: 10.1016/j.archoralbio.2010.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Age and gender influence on maximal bite force and masticatory muscles thickness

Abstract: The present study aimed investigate the age and gender influence on maximal molar bite force and at outlining the criteria for normal masticatory muscle development in a sample of 177 Brazilian Caucasian dentate individuals aged 7-80 years divided into five age groups: I (7-12 years), II (13-20 years), III (21-40 years), IV (41-60 years), and V (61-80 years). Except for Group V, which comprised nine women and eight men, all groups were equally divided in respect to gender (20 M/20 F). Bite force was recorded w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
191
1
59

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 242 publications
(287 citation statements)
references
References 17 publications
22
191
1
59
Order By: Relevance
“…When analyzing the MBF results, we found that men showed higher MBF compared to women, regardless of the side, and these findings are in agreement with studies by Bonakdarchian, Askari and Askari [7], Palinkas et al [8], Koç, Dogan and Bek [9], de Abreu et al [10], Takaki, Vieira and Bommarito [11], and Roldán et al [12].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…When analyzing the MBF results, we found that men showed higher MBF compared to women, regardless of the side, and these findings are in agreement with studies by Bonakdarchian, Askari and Askari [7], Palinkas et al [8], Koç, Dogan and Bek [9], de Abreu et al [10], Takaki, Vieira and Bommarito [11], and Roldán et al [12].…”
Section: Discussionsupporting
confidence: 81%
“…These findings are not in agreement with Bonakdarchian et al [7], Palinkas et al [8], de Abreu et al [10], which did not find any significant difference between the right and left sides in both sexes, in individuals with absence of sagittal alterations.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…The measures were taken from the mandibular right and left first molar regions, where the maximal bite force occurs [9,10]. During the procedure, the patients sat on a chair, with the arms extended along the body and the hands lying on the thighs, and were instructed and trained on how to bite the dynamometer, to ensure the reliability of the procedure.…”
Section: Bite Forcementioning
confidence: 99%